2019
DOI: 10.1007/s00330-019-06579-w
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding skull radiographs in infants with suspected inflicted injury who also undergo head CT: “a no-brainer?”

Abstract: Objectives To assess whether head CT with 3D reconstruction can replace skull radiographs (SXR) in the imaging investigation of suspected physical abuse (SPA)/abusive head trauma (AHT). Methods PACS was interrogated for antemortem skeletal surveys performed for SPA, patients younger than 2 years, SXR and CT performed within 4 days of each other. Paired SXR and CT were independently reviewed. One reviewer analysed CT without and (3 months later) with 3D reconstructions. SXR and CT expert consensus review formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 14 publications
2
19
1
1
Order By: Relevance
“…The sensitivity for X‐rays was only slightly lower than that reported by Cattaneo et al [8], where X‐rays detected only a third of all pediatric skull fractures. Sensitivities for CTs and X‐rays in the present study were also lower than those reported by Martin et al [12] who found sensitivities of 81% for CTs and 77‐81% for X‐rays, and Culotta et al [5] who cited a 97% sensitivity for CTs and 90% for X‐rays. However, both authors used either the CT or X‐ray scans as the gold standard, not osteological analysis.…”
Section: Discussioncontrasting
confidence: 89%
See 4 more Smart Citations
“…The sensitivity for X‐rays was only slightly lower than that reported by Cattaneo et al [8], where X‐rays detected only a third of all pediatric skull fractures. Sensitivities for CTs and X‐rays in the present study were also lower than those reported by Martin et al [12] who found sensitivities of 81% for CTs and 77‐81% for X‐rays, and Culotta et al [5] who cited a 97% sensitivity for CTs and 90% for X‐rays. However, both authors used either the CT or X‐ray scans as the gold standard, not osteological analysis.…”
Section: Discussioncontrasting
confidence: 89%
“…In addition, most temporal fractures, and many parietal and frontal fractures close to the vertex of the skull, such as the parietal fracture seen in Figure 1, were undetected using X‐rays and Lodox ® . The low sensitivities for detecting skull fractures in the correct locations may, in the case of CTs, be the result of the orientation of the scan slice with respect to that of the fracture [8,12]. In the case of X‐rays and Lodox ® scans, superimposition of bones, very thin or incomplete fractures, and the limited three‐views of the skull (anteroposterior and left and right lateral) may limit the detectability of fractures and cause the underestimation of the number of fractures present [4,7,8,24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations